Advantages of Peer Tutoring for Students with Hearing Impairment: A Survey of Special Education Teachers’ Perceptions - Sheza Amjad; Muhammad Usman Zia (Social Science Review Archives, 2025)
This study explores the perceptions of the teachers about academic, social and personal advantages of peer tutoring for students with hearing impairment. Survey design was employed for data collection using a self-developed, expert validated questionnaire. The questionnaire was consisting of two sections: demographic variables and 16 statements examining the perceptions of teachers. The teachers of students with hearing impairment from special education schools in Punjab, Pakistan were considered to be the population of the study, with a sample of 66 teachers randomly selected as the sample. The data was collected online and data analysis utilized descriptive and inferential statistics. A broad agreement on the impact of peer tutoring on educational achievement, social skills and personal development was found with no significant differences in the opinions of teachers on the basis of gender.